Crystallographic phases, phase transitions, and barrier layer formation in (1 - x) [Pb(Fe1/2Nb1/2)O3]-xPbTiO3 - Singh S.P.; Singh A.K.; Pandey D.; Sharma H.; Parkash O. (My University, 2025)
Powders of (1 - x) Pb(Fe1/2Nb1/2)O 3-xPbTiO3 (PFN-PT) with x = 0.00, 0.10, 0.13, 0.15, 0.20, and 0.25 were prepared by the conventional solid-state route. Structure of PFN-PT was tetragonal for x ≥ 0.10, which indicates that the morphotropic phase boundary (MPB) may be between 0 < x < 0.10. The nature of phase transition in PFN-PT changed from diffuse ferroelectric to relaxor ferroelectric to normal ferroelectric on increasing the PT content. The effect of the PT content and sintering temperature on barrier layer formation in the PFN-PT system was studied using complex impedance spectroscopy. With increasing PT content, the possibility of the barrier layer formation decreased while with increasing sintering temperature, the barrier layer formation was promoted.